2020
DOI: 10.1017/asr.2019.52
|View full text |Cite
|
Sign up to set email alerts
|

Refugees, Foreign Nationals, andWageni: Comparing African Responses to Somali Migration

Abstract: Abstract:Host governments have responded to the migration of Somali refugees throughout Africa in recent decades in different ways. Kenyan policymakers have treated Somalis primarily as a security threat, imposing restrictions on them that especially target this group. In South Africa, where economic and political competition fuel xenophobia, Somalis are part of a larger foreign national population that is seen as having disproportionate economic influence. However, Somali Bantus have been welcomed in Tanzania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Host citizens in both countries generally hold negative stigmatized views of refugees. For example, in Kenya, security concerns surrounding refugees are pervasive, with many associating them with terrorism and conflict (Audette et al, 2020; Aukot, 2003; Whitaker, 2020). Likewise, Tanzania has enacted increasingly repressive policies such as forced repatriation and even state-sanctioned torture citing security fears.…”
Section: Case Selection Of Kenya and Tanzaniamentioning
confidence: 99%
“…Host citizens in both countries generally hold negative stigmatized views of refugees. For example, in Kenya, security concerns surrounding refugees are pervasive, with many associating them with terrorism and conflict (Audette et al, 2020; Aukot, 2003; Whitaker, 2020). Likewise, Tanzania has enacted increasingly repressive policies such as forced repatriation and even state-sanctioned torture citing security fears.…”
Section: Case Selection Of Kenya and Tanzaniamentioning
confidence: 99%
“…These traditions influence where and when people migrate in response to natural environmental change, conflict, or changing economic opportunity. Hauer et al (2020) found that victims fleeing the Japanese earthquake and tsunami of 2011 followed “the pre‐existing migration system.” Whitaker (2020) describes Somali Bantus seeking political asylum in Tanzania due to historical and cultural connections that smoothed paths to citizenship.…”
Section: Migration Processesmentioning
confidence: 99%
“…Kenny and Miller (2020) noted that individuals who leave their country of origin for various reasons are processed in their host country, where their details are captured on a national database and they are given temporary residence permits that are renewed periodically while awaiting adjudication of their asylum status. Once their application for asylum has been approved, they are recognised as refugees and receive documentation that enables them to live and work in the country (Whitaker, 2020). South Africa's history of migration dates back to the mid-19th century.…”
Section: Migration In Pre-and Post-apartheid South Africamentioning
confidence: 99%